2015
DOI: 10.1016/j.anai.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anxiety and depression on outpatients with asthma

Abstract: The present real-life study indicates that anxiety and depression are common and relevant comorbidities in asthmatic outpatients and are associated with uncontrolled asthma and lower ACT scores. Thus, assessment of comorbid mental disorders should be performed in common practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(93 citation statements)
references
References 45 publications
8
74
1
10
Order By: Relevance
“…We also found that psychological disturbance was important in the Chinese population. We identified 15.4% (n=57) of patients with psychological symptoms, which is similar to other studies (16,17). There was a higher prevalence of psychological symptoms in patients with uncontrolled or severe asthma, which is also similar to other studies (18).…”
Section: Discussionsupporting
confidence: 79%
“…We also found that psychological disturbance was important in the Chinese population. We identified 15.4% (n=57) of patients with psychological symptoms, which is similar to other studies (16,17). There was a higher prevalence of psychological symptoms in patients with uncontrolled or severe asthma, which is also similar to other studies (18).…”
Section: Discussionsupporting
confidence: 79%
“…Up to 18% of asthma patients have depression, while 11%‐37% have anxiety . Patients with difficult asthma have even higher rates of depression and anxiety, at 31% and 81% for depression and anxiety respectively in one study …”
Section: How Common Are Comorbidities In Difficult Asthma?mentioning
confidence: 92%
“…Asthma is significantly associated with psychiatric disorders [1], especially depression that has been consistently reported to be prevalent in asthmatic patients [2–4]. Adeyeye et al [5] indicated that depression is the most important factor independently associated with asthma-related quality of life.…”
Section: Introductionmentioning
confidence: 99%